Bad mothers : regulations, representations, and resistance - Miller, Michelle Hughes; Hager, Tamar, 1960-; Bromwich, Rebecca (Demeter Press, 2017)
While the image or construct of the ""good mother"" has been the focus of many research projects, the ""bad mother, "" as a discursive construct, and also mothers who do ""bad"" things as complicated, agentic social actors, have been quite neglected, despite the prevalence of the image of the bad mother across late modern societies. The few researchers who address this powerful social image point out that bad mothers are culturally identified by what they do, yet they are also socially recognized by who they are. Mothers become potentially bad when they behave or express opinions that diverge f.